Human Serum Complement C3 and Factor H in the Syndrome of Hemolysis, Elevated Liver Enzymes, and Low Platelet Count - ARIKAN, İZZET HAKKI; ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF (WILEY, 2009)
Problem Hemolysis, elevated liver enzymes, and low platelet count syndrome (HELLP syndrome) is a life-threatening variant of severe pre-eclampsia in pregnant women. The complement system may play a role in the pathogenesis of this condition. We sought to determine serum complement 3 (C3) levels and its regulatory protein complement factor H (FH) in the HELLP syndrome. Method of study Twenty-two pre-eclamptic patients with HELLP syndrome (mean age: 27.8 +/- 6.2 years), 21 pre-eclamptic patients without HELLP syndrome (mean age: 27.5 +/- 6.8 years) and 24 normotensive, healthy pregnant women (mean age: 26.1 +/- 4.4 years) were included in this study. Serum concentrations of C3 and FH were measured in all participants. Results Concentrations of C3 and FH did not differ significantly between the study groups. In patients with the HELLP syndrome, FH levels were positively associated with platelet count. Conclusion These findings did not support a major role of complement activation in the HELLP syndrome. In patients with HELLP, lower levels of FH are correlated with a reduced platelet count.
Keywords: Complement; factor H; HELLP syndrome; pre-eclampsia; PREECLAMPSIA; MANAGEMENT; DIAGNOSIS; PROTEIN; HELLP